2024
DOI: 10.1111/nbu.12670
|View full text |Cite
|
Sign up to set email alerts
|

The double burden of malnutrition in individuals: Identifying key challenges and re‐thinking research focus

Agklinta Kiosia,
Aygul Dagbasi,
James A. Berkley
et al.

Abstract: The ‘double burden of malnutrition’ is a global health challenge that increasingly affects populations in both low‐ and middle‐income countries (LMICs). This phenomenon refers to the coexistence of undernutrition and overweight or obesity, as well as other diet‐related non‐communicable diseases, in the same population, household or even individual. While noteworthy progress has been made in reducing undernutrition in some parts of the world, in many of these areas, the prevalence of overweight and obesity is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…The interaction between these conditions, their associations with behavioral factors, and social determinants are still scarce and require investigation [ 8 ]. While it is recognized that malnutrition can manifest in different ways, studies on the prevalence of DBM have mainly observed the coexistence of low weight and overweight/obesity at the population level [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between these conditions, their associations with behavioral factors, and social determinants are still scarce and require investigation [ 8 ]. While it is recognized that malnutrition can manifest in different ways, studies on the prevalence of DBM have mainly observed the coexistence of low weight and overweight/obesity at the population level [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other nutritional deficiencies are often less explored, such as micronutrient deficiencies (e.g., vitamin D deficiency) and how these conditions coexist at the individual level [ 30 , 31 , 32 ]. Especially among adolescents in LMIC, where the DBM may pose an even greater challenge due to unfavorable socioeconomic conditions resulting from social disparities that significantly influence health patterns [ 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%